PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN MENGGUNAKAN MEDIA ANIMASI PADA MATA PELAJARAN KONSTRUKSI BETON DI PROGRAM KEAHLIAN TEKNIK KONSTRUKSI BATU BETON SMK NEGERI 2 PURWOKERTO - Nandja, Karsukmia (Sainteks, 2012)
Classroom Action Research aims to improve learning outcomes of students through the use of three-dimensional animation media in direct learning. The subject of this study is 32 Class XI students of SMK Negeri 2 Purwokerto Semester I Year Lessons2011/2012. Implementation of this study consisted of two cycles, each cycle consists of phases: planning (planning), implementation (acting); observation (observing), reflections (reflecting). The data collected in the form of learning outcomes of students were analyzed using descriptive statistical analysis, while data in the form of learner activity collected using observation sheets were analyzed qualitatively. The results of data analysis are as follows: (1) Concrete Construction Percentage learning outcomes are grouped into five categories after the cycle I are both very good 29,03%, good 32,25%, sufficient 26,82%, and less 12,90%, with an average value 69,35, score the highest 88,45, the lowest value 50,25, standard deviation 11,752, and exhaustiveness class 58,06%. (2) Percentage of Concrete Construction learning outcomes are grouped into five categories after the second cycle is 43,750% excellent, good 53,125%, enough 03,125%, with an average value 80,82, the highest score 96,65, lowest score 65,00, standard deviation 9,018, and exhaustiveness class 90.63%. From the results of this study can be concluded that the use of three-dimensional animation media can improve learning outcomes learners Concrete Construction TKBB class XI-1 SMK Negeri 2 Purwokerto, from the average value 69,35becomes 80,82.Keywords :Three-Dimensional Animation Media, Learning Outcomes.